Peran Trichoderma spp. sebagai Agen Biokontrol pada Penyakit Rebah Semai dan Biostimulan Kedelai: The Role of Trichoderma spp. as a Biocontrol Agent of Damping Off Disease and Soybean Biostimulant - Maknunin, Lu'lu'il; Abdul Latief Abadi; Fery Abdul Choliq (Jurnal Fitopatologi Indonesia, 2024)
The Role of Trichoderma spp. as a Biocontrol Agent of Damping Off Disease and Soybean Biostimulant   Domestic demand for soybeans in Indonesia continues to increase each year, yet the average production has declined. To meet national needs, the government must even import soybeans. One of the causes of low soybean production is damage from plant pests and diseases, particularly damping-off caused by Sclerotium rolfsii, which can lead to total plant death under severe infection. One promising, environmentally friendly, and cost-effective approach to disease management is the use of biological control agents such as Trichoderma spp., which function not only as biocontrol agents but also as biostimulants. This research was conducted at the Plant Pest and Disease Laboratory, Faculty of Agriculture Brawijaya University and Central Laboratory of BALITKABI for in vitro experiments and in vivo study located at a greenhouse of Agriculture Experimental Land Brawijaya University, Jatimulyo, Lowokwaru, Malang. A completely randomized design was used with five treatments and five replications. Applications of Trichoderma harzianum and T. asperellum, either individually or in combination, successfully reduced the incidence and severity of damping-off disease by 14% to 26.6% under field conditions. These treatments also increased the total phenolic content of the plants, indicating enhanced resistance, thus supporting the role of Trichoderma as an effective biocontrol agent. In addition, the combined application of Trichoderma species significantly increased the number of soybean leaves, indicating a biostimulant effect.